Work Stress Hampering Employee Performance During COVID-19: Is Safety Culture Needed? - Saleem, Farida; Malik, Muhammad Imran; Qureshi, Saiqa Saddiqa (Frontiers in Psychology, 2021)
During uncertain situations such as COVID-19 partial lockdown, maintaining satisfactory levels of employees performance is an important area of concern for many organizations. The current study examines the relationship of work stress due to COVID-19 and employee performance. Using social exchange theory, safety culture is presented as a moderator for stress and performance relationships. A sample of 213 bank employees was collected using a convenient sampling method. Data were analyzed using stepwise linear regression and PROCESS Macro by Hayes (2013). Results revealed that stress due to COVID-19 has negative impact on task and contextual performance and positive impact on adaptive performance. Similarly, the prevalence of safety culture significantly moderates the stress and performance relationships.